Hubungan Perilaku Minum Tablet Zat Besi pada Remaja Putri dengan Kadar Hemoglobin - Ery Susanti; Maria Ulfa (Journal of Ners and Midwifery, 2014)
Most of the cases of anemia in Indonesia are caused by the lack of iron in the body since the iron existing in the food consumed does not meet the need. The need of the iron of female teenager is used to replace the lost of the iron during the menstrual cycle. The purpose of this study was to identify relationship between Fe tablet drinking behavior in teenagers with the level of hemoglobin. Method: The research design was quasi eksperiment using one-shot case study research.Â  The research sample was 19 student at STIKes Patria Husada Blitar at May 24th until Juni 22nd 2012, its choosed with purposive sampling. The data collected by observation using checklist. The analisys using spearman rank, with significant level â‰¤ 0,05. Result: The result showed that drinking behavior of Fe tablets were not good with the mild anemia hemoglobin level was 26.3 with p-value of 0.009 was obtained. Discussion: A good drinking behavior of iron tablets will result in the raise of hemoglobin levels formed, so that anemia could be prevented.